Perang, Repetisi, dan Kosmos: Sebuah Etnografi tentang Perang pada Masyarakat Lembah Agung Baliem - Prasetyo, Aji Dwi (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2020)
War, admittedly or not, has always been a "way out" for archaic society or modern society. As an inevitable thing to all form of culture, war have the same role and function of finding new equilibrium. Through this paper, the author tries to understand war through the cultural framework of the Baliem Valley community. Reading war from "the authentic" will make it easier for us to read various forms of war in various cultures and various periods. This article discusses the traditional war of the Baliem Community. War is something that cannot be separated in the whole life of the Baliem Valley Community. Without war, the affirmation of Baliem's human identity is incomplete. Social relations and kinship between the people of the Baliem Valley are strengthened by the existence of war. War connects the present and the past while placing each individual in a cosmic balance.